PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN, UMUR PERUSAHAAN DAN PROFITABILITAS TERHADAP KINERJA INTELLECTUAL CAPITAL SEKTOR KEUANGAN - Dewi Khasanah (Parsimonia - Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine whether there is an effect of institutional ownership, size, company age and profitability on intellectual capital performance in the financial sector listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The sample of this study consists of financial sector companies that have gone public and the amount of data that matches the sample criteria is 210 data consisting of 70 companies. This study uses panel data regression with eviews 10 program to examine the effect of each independent variable with the dependent. The results of the study indicate that institutional ownership, size, age and profitability have no effect on intellectual capital performance. In addition, this study also cannot support the theory proposed by Wernerfelt (1984), namely resources-based theory.